What Motivated Them to Assume Leadership Roles - Jingjing Wu; Weiling Liu (International Journal of Librarianship (IJoL), 2025)
This study explores the motivations of former presidents of the Chinese American Librarians Association (CALA) in assuming leadership roles within the organization. Through inductive thematic analysis of interview transcripts, the study identifies key motivations that drove these individuals to engage in CALA’s leadership and the impact of their experiences on their professional growth and development. The analysis, supported by generative AI tools (ChatGPT 4o mini and Claude Haiku with concise responses), reveals nine core themes, categorized into three overarching groups: Professional Development and Personal Growth, Advocacy, Influence, and Responsibilities, and Organizational Culture. These themes encompass factors such as professional development, career advancement, cultural empowerment, mentorship, and a desire to give back to CALA. The findings offer valuable insights for fostering leadership engagement within CALA and similar professional organizations, highlighting the desire for giving back and cultural connections and empowerment. Additionally, the study reflects on the use of generative AI in qualitative research, demonstrating its potential to enhance the efficiency and rigor of thematic analysis.